Optimization of Neutralize Crude Gypsum (NCG) Quality through Flash Dryer Utilization at Plant IIIA PT. Petrokimia Gresik - Rohmad Taufiqi; Rensa Arnas Yunarwan; Shanti Larissa; Rachmad Ramadhan Yogaswara (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2023)
Neutralized Crude Gypsum (NCG) is produced as by-product from phosphoric acid plant at Plant IIIA PT. Petrokimia Gresik. The aims of this study are finding main cause and solution from Neutralized Crude Gypsum (NCG) quality reduction at PT. Petrokimia Gresik Plant IIIA. This research is done by qualitative analysis in order to collect the data of gypsum quality every month. Gypsum characteristics is observed by some instrument analysis such as spectrophotometry UV-Vis, atomic absorption spectrometry (AAS), and gravimetry technique. NCG was taken at different point on gypsum disposal land and different times to analyze its quality change. NCG sample shows decreased quality having higher moisture content at September that does not comply the SNI 715:2016 about gypsum minimum quality. Flash dryer is designed in this study to reduce the water concentration inside the surface of gypsum particle. Flash dryer design can lower the H2O content based on material balance analysis at finishing sector Plant IIIA unit.